France : Financial Sector Assessment Program-Technical Note on Housing Prices and Financial Stability. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
This technical note examines housing prices and financial stability in France. The note highlights that sharply rising housing prices have caused concerns about mortgage credit risk and the stability of the financial system, particularly if the macroeconomic environment were to deteriorate further. France's housing market proved resilient during the crisis, declining by about 9 percent from its precrisis peak before rebounding since mid-2009 to surpass its precrisis peak. This resilience has reflected a confluence of fundamental, macroeconomic, financial, and asset allocation factors that have caused the demand for housing to remain well in excess of supply.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet